Ents, elves, and Eriador : the environmental vision of J.R.R. Tolkien - Dickerson, Matthew T., 1963-; Evans, Jonathan D. (Jonathan Duane), 1954- (Lexington, Ky. : University Press of Kentucky, 2006)
With a Foreword by John Elder and an Afterword by Tom Shippey Though not often recognized as environmental or agrarian literature, the writings of J.R.R. Tolkien demonstrate a complex and comprehensive ecological philosophy. The ecology of Middle-earth portrayed in The Hobbit, The Lord of the Rings, and The Silmarillion brings together three potent and convincing elements of preservation and conservation--sustainable agriculture and agrarianism, horticulture independent of utilitarianism, and protection of unspoiled wilderness. Throughout his work, Tolkien reveals his vision of the natural world and environmental responsibility. Ents, Elves, and Eriador examines the underlying environmental philosophy in Tolkien's major works as well as his lesser-known stories and essays. Matthew Dickerson and Jonathan Evans evaluate Tolkien's writing, especially his Middle-earth legendarium, in the context of modern environmental literature. The authors compare Tolkien's work with that of some of the most important environmental scholars and nature writers of the past century, including Wendell Berry, John Elder, Aldo Leopold, and Scott Sanders, highlighting Tolkien's intellectual depth. A vital contribution to environmental literature and an important addition to Tolkien scholarship, Ents, Elves, and Eriador offers all fans of Tolkien a new way to understand his writings.
Varda, Yavanna, and the value of creation -- Gandalf, stewardship, and tomorrow's weather -- Hobbits and the agrarian society of the Shire -- Horticulture and the aesthetic of the elves -- Woods, wildness, and the feraculture of the ents -- The necessity of margins in Middle-Earth's mingled ecologies -- The ecology of Ham, Niggles' Parish, and Wootton Major -- Three faces of Mordor -- Rousing the Shire -- Environmentalism, transcendence, and action.
Includes bibliographical references (pages 273-298) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Knowledge -- Environmental sciences; Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Tolkien, J. R. R. -- 1892-1973; Tolkien, John Ronald Reuel, -- (1892-1973) -- Critique et interprétation.; Tolkien, John R. R; Ecology in literature; Nature in literature; Human ecology in literature; Middle Earth (Imaginary place); Environmentalism; Ecocriticism; Environmental literature -- History and criticism; Nature dans la littérature.; Écologie humaine dans la littérature.; Terre du Milieu (Lieu imaginaire); Environnementalisme; Écocritique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Science Fiction & Fantasy; Environmental sciences; Ecocriticism; Ecology in literature; Environmental literature; Environmentalism; Human ecology in literature; Middle Earth (Imaginary place); Nature in literature; Ökologie; Écologie -- Dans la littérature.; Nature -- Dans la littérature.; Terre du Milieu (lieu imaginaire); Ekologi i litteraturen; Naturen i litteraturen; Ekokritik; Criticism, interpretation, etc; Electronic books